The Relationship between Career Maturity and Self-confidence of Baitul Tamwil Muhammadiyah Employees During the COVID-19 Pandemic in Padang City, Indonesia - Murisal, Murisal; Hermawati, Hermawati; Alfaiz, Alfaiz; Sari, Azmatul Khairiyah (Counsellia: Jurnal Bimbingan dan Konseling, 2022)
This study aims to describe the career maturity of Baitul Tanwil Muhammadiyah (BTM’s) employees during the COVID-19 pandemic that affects their confidence in the Syariah economy in Padang. This study was conducted with a descriptive quantitative method and the population was all employees of BTM in West Sumatra totaling 39. The number of samples was determined using the convenience sampling technique, namely based on the ease of finding the participants (Guilford & Frucher, 1978), while the instrument used was a career maturity scale consisting of 51 statement items. This scale is based on career maturity dimensions, namely Planning, Exploration, Decision Making, and World of Work, according to Thompdon et al., (1981). The results showed that there was a significant positive relationship between career maturity and the confidence of baitul tanwil employees in taqwa Muhamadiyah with r = 0.499 and p = 0.000 (p <0.05) which means H0 is rejected or Ha is accepted. Moreover, a value of 0.202 was obtained which means that there is a 20.2% contribution of career maturity to self-confidence, while the remaining 79.8% is determined by other factors and aspects.